1996
DOI: 10.1677/joe.0.1500169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term food reduction on the hypothalamus-pituitary-thyroid axis in male and female rats

Abstract: The reduced thyroid activity during short-term starvation is associated with a lowered hypothalamic synthesis and secretion of TRH. However, little is known about the cause of the reduced thyroid function during prolonged malnutrition. We have therefore studied the effects of food reduction to one-third of normal (FR33) on the hypothalamus-pituitary-thyroid axis of male and female Wistar rats. After 3 weeks body weights of FR33 rats were almost 50% lower than those of controls. In both sexes, FR33 caused marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 0 publications
2
32
1
1
Order By: Relevance
“…Thyroid hormones are reduced by hypercortisolism associated with chronic disease [75] as well as restraint stress [76] and food restriction [77,78], effects that may be mediated through a reduction in hypothalamic TRH expression. However, other data indicate this decrease induced by food restriction [47] and stress [48] may occur independent of changes in TRH expression. Because we did not observe differences in T4, the decrease in T3 may be due to a disruption in type 2 deiodinase activity (D2).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thyroid hormones are reduced by hypercortisolism associated with chronic disease [75] as well as restraint stress [76] and food restriction [77,78], effects that may be mediated through a reduction in hypothalamic TRH expression. However, other data indicate this decrease induced by food restriction [47] and stress [48] may occur independent of changes in TRH expression. Because we did not observe differences in T4, the decrease in T3 may be due to a disruption in type 2 deiodinase activity (D2).…”
Section: Discussionmentioning
confidence: 98%
“…Insulin and glucose were measured as indices of energy homeostasis [46]. Finally, the thyroid hormones, triiodothyronine (T3) and thyroxine (T4), were measured, as these hormones are decreased by reduced food intake [47] and exposure to chronic stressors [48].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The results suggest that although most of the association between TSH and cognitive abilities may be due to shared change variation, TSH may exert a direct impact on episodic memory. It is suggested that the mechanism for such effects are increased cortisol levels, known to affect episodic memory functioning in particular (Lupien et al, 1994;van Haasteren et al, 1996). In order to further clarify this topic, it is necessary to expand the age range under scrutiny to cover both younger and older participants, and to add indicators of both relevant thyroid indexes (TSH and thyroxine), and steroid hormone levels.…”
Section: Longitudinal Evidence 22mentioning
confidence: 99%
“…Importantly, thyroid hormones increase the response of the beta-adrenergic receptor to norepinephrine, which may serve as an adaptive mechanism of neuromodulation (Whybrow and Prange, 1981;Dratman and Gordon, 1996). More specifically, low TSH levels are also associated with elevated steroid hormone levels within the hypothalamus-pituitary-adrenal axis (van Haasteren et al, 1996). Increased levels of cortisol, which is part of this circuitry, may result in hippocampal cell loss and impair episodic memory performance (Lupien et al, 1994).…”
mentioning
confidence: 99%
“…Many studies have reported that food deprivation or restriction elevates plasma glucocorticoid levels (GarciaBelenguer et al, 1993;Kiss et al, 1994;van Haasteren et al, 1996). Furthermore, Chang et al (2002) reported that food deprivation enhances enzyme activity of P450 11beta and elevates plasma corticosterone level.…”
Section: Et Al 2001mentioning
confidence: 99%